Future scenarios of commercial internet content delivery - Nan Zhang; Heikki Hämmäinen; Tapio Levä (International Telecommunications Society (ITS), 2012)
The Internet content volume is growing rapidly. As a consequence, the current Internet model struggles with scalability and usability requirements. To better meet the demand, technical solutions utilising caching and name-based routing are being developed. This paper aims at identifying the key forces, both trends and uncertainties that affect the evolution of the heavy commercial Internet content delivery. To bound the uncertainties, four possible future scenarios are constructed and their effect on the key stakeholders is described briefly. The value of identifying the future scenarios is to define the winning business roles and actors per scenario and, subsequently, the winners' preferences in choosing the most attractive content delivery architectures.
Keywords: 330; scenarios; Internet content delivery; commercial; video; information-centric networking; content delivery network